2006
DOI: 10.1007/s10531-005-0768-6
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Hotspots and Conservation Priorities in the Campo-Ma’an Rain Forests, Cameroon

Abstract: Abstract. Until recently, patterns of species richness and endemism were based on an intuitive interpretation of distribution maps with very limited numerical analyses. Such maps based solely on taxonomic collections tend to concentrate on collecting efforts more than biodiversity hotspots, since often the highest diversity is found in well-collected areas. During the last decades, there has been an overwhelming concern about the loss of tropical forest biological diversity, and an emphasis on the identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 9 publications
0
32
0
6
Order By: Relevance
“…The Southern Ngovayang is among the most species-rich sites of the range of small mountains bordering the gulf of Guinea, with a mean of 110 tree species ha -1 ( (White 1983;Davis et al, 1994;van Gemerden et al 2003;Tchouto et al 2006Tchouto et al , 2009. Furthermore, the Fisher's a value for Ngovayang is significantly higher (KruskalWallis test, P = 0.039) than that for forests of Korup National Park (mean of 30.5), widely known for its high diversity and endemism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Southern Ngovayang is among the most species-rich sites of the range of small mountains bordering the gulf of Guinea, with a mean of 110 tree species ha -1 ( (White 1983;Davis et al, 1994;van Gemerden et al 2003;Tchouto et al 2006Tchouto et al , 2009. Furthermore, the Fisher's a value for Ngovayang is significantly higher (KruskalWallis test, P = 0.039) than that for forests of Korup National Park (mean of 30.5), widely known for its high diversity and endemism.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of Lower-Guinea species in different sites is highest near the coast (23% for Dja and central Gabon forests to 43% for Monte Alen, Ngovayang and Korup). In Campo-Ma'an National Park, identified as a biodiversity hotspot due to its high levels of species richness and endemism (Tchouto et al 2006(Tchouto et al , 2009, the proportion of Lower Guinea endemics (including Cameroonian endemics) is lower (29%), but this apparent difference may Table 4 Comparison of Ngovayang tree diversity with that of other forest sites in Central Africa and the Neotropics, based on 1-ha (100 m 9 100 m) plots, by decreasing values of Fisher's a simply reflect the inclusion in the inventory for this site of secondary-forest and swampy environments, which harbor numerous species with large geographic ranges. Additional indications of high endemism in the Massif come from studies focusing on the distribution of particular taxonomic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These records, however, suffer spatial and temporal shortcomings when mapping the geographic range of species, mainly due to uneven historical sampling techniques (Townsend Peterson and Watson 1998). Some studies have shown that maps based solely on taxonomic collections tend to focus on concentrated areas where data was collected more than on biodiversity hotspots since the greatest diversity is usually found in well-collected areas (Tchouto et al 2006). In this study, a combination of herbarium specimens and various relevant references was used to avoid this problem and to ensure the scope and precision of the distribution data was reliable.…”
Section: Distribution Data Limitations and Solutionsmentioning
confidence: 99%
“…Comparable measurements of species richness along the coastal dune gradient, which evidence rare and endangered species, can help answering crucial questions for ecosystem management such as which community best contributes to total species diversity or which are the priority habitats to propose for conservation planning. (Metzger et al 2005;Tchouto et al 2006). While rare and endangered species may contribute little to ecosystem function, they constitute the keystone of many conservation programs such as those promoted by EU Directive 92/43.…”
Section: Introductionmentioning
confidence: 99%